New Markers for Ventricular Repolarization in Coronary Slow Flow: Tp‐e Interval, Tp‐e/QT Ratio, and Tp‐e/QTc Ratio. Issue 4 (30th September 2014) - Karaman, Kayihan; Altunkaş, Fatih; Çetin, Mustafa; Karayakali, Metin; Arısoy, Arif; Akar, Ilker; Zencir, Cemil; Aygüç, Barış; Çelik, Ataç
<x xml:space="preserve">Abstract</x> Background Coronary slow flow (CSF) is characterized by normal or near‐normal coronary arteries with delayed opacification of the distal vasculature that it may cause angina pectoris, acute myocardial infarction, life‐threatening arrhythmias, and sudden cardiac death. The Tp‐e interval, Tp‐e/QT ratio, and Tp‐e/QTc ratio are also known as predictors of ventricular arrhythmogenesis. The aim of this study was to assess ventricular repolarization in patients with CSF by using Tp‐e interval, Tp‐e/QT ratio, and Tp‐e/QTc ratio. Methods This study included 50 patients with CSF and 51 control subjects. Coronary flow rates of all subjects were documented by thrombolysis in myocardial infarction (TIMI) frame count (TFC). Tp‐e interval, Tp‐e/QT ratio, and Tp‐e/QTc ratio were measured from the 12‐lead electrocardiogram. These parameters were compared between groups. Results In electrocardiographic parameters analysis, QT, QTc, QTd, and QTcd were significantly increased in CSF patients compared with the control subjects (P < 0.001, P = 0.019, P < 0.001, P < 0.001, respectively). The Tp‐e interval, Tp‐e/QT ratio, and Tp‐e/QTc ratio in the CSF patients were significantly higher than those in the control subjects (Tp‐e: 117 ± 21 milliseconds [ms] vs 96 ± 16 ms, P < 0.001; Tp‐e/QT: 0.30 ± 0.06 vs 0.27 ± 0.06, P = 0.005; Tp‐e/QTc: 0.27 ± 0.06 vs 0.24 ± 0.05, P < 0.001). In the multivariate analysis, increased Tp‐e and Tp‐e/QT ratio were associated with CSF. Conclusions Our study revealed that when compared to the control subjects, Tp‐e interval, Tp‐e/QT ratio, and Tp‐e/QTc were significantly increased in the CSF patients.